Associação entre autopercepção da capacidade mastigatória e sarcopenia em idosos vivendo na comunidade - Krassmann, Ariane Soares (2020)
Aging is a physiological process that imposes changes in body composition, which requires care in order to prevent frailty and to maintain functional capacity and quality of life. Considering that chewing ability is paramount to maintain balanced nutrients intake, tooth loss, lack of rehabilitation or poorly adapted dental prosthesis may impair this function, with harms to individuals’ general health as well. Sarcopenia, defined as a degenerative loss of skeletal muscle mass, with progressive decrease of muscle mass, strength and performance, leading to negative impacts on older subjects’ health. This study aimed to verify the association between self-perceived chewing capacity and sarcopenia in Brazilian’s southern older subjects. It consists of a cross-sectional study, nested in a cohort, on the association between oral conditions and general health of the elderly living in the community, in the city of Carlos Barbosa, Rio Grande de Sul, Brazil. Data from the second follow-up, carried out in 2012, including 389 older adults were analyzed. Sociodemographic and behavioral characteristics, general and oral health conditions were collected by self-report questions comprised in a standardized questionnaire, in addition to oral and anthropometric assessments. The presence of sarcopenia was considered the outcome and was assessed by the construction of a variable considering the association among calf circumference, grip strength and gait speed. Sample descriptive analyses was carried out through absolute and relative frequencies. Associations with the outcome were performed using hierarchical Poisson regression, adjusting for confounding variables with estimation of crude and adjusted prevalence ratios and a 95% confidence interval. All analyzes were performed using the SPSS software. The sample prevalence of sarcopenia was 19.8%. The higher prevalence ratios of sarcopenia in the elderly were found among unmarried older adults (PR = 2.14; 95% CI 1.45-3.16), with a lower education level (PR = 2.16; 95 % CI 1.18-3.93), presenting comorbidities (PR = 1.79; 95% CI 1.08-2.97) and with worse perception of chewing capacity (PR = 1.55; 95% CI 1.04-2.31). The findings suggest that there is association between worse self-perceived chewing capacity and sarcopenia in older adults, in addition to sociodemographic and general health factors associated with the outcome.